2003
DOI: 10.1016/s0378-1097(03)00788-2
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis67-kDa fimbriae induced cytokine production and osteoclast differentiation utilizing TLR2

Abstract: Porphyromonas gingivalis, a major etiological agent of adult periodontitis, has two distinctly different types of fimbriae on the cell surface. The major fimbriae, which consist of a 41-kDa fimbrillin of P. gingivalis ATCC 33277, have been known to induce inflammatory cytokine production in murine peritoneal macrophages. In this study, we examined the effects of the minor fimbriae of P. gingivalis, composed of a 67-kDa fimbrillin, on cytokine production in murine peritoneal macrophages and the ability to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 34 publications
1
46
0
3
Order By: Relevance
“…Alveolar bone loss elicited by Porphyromonas gingivalis shares many features of lysis attending OM. Cytokine release (166) as well as induction of RANKL downstream of TLR2 and NOD2 are the prominent pathways leading to osteoclast activation in periodontitis (167,168). IL-17 is also markedly increased in periodontitis and appears to be an important factor in both inflammation and osteolysis of the periodontal tissue (169).…”
Section: Infection-associated Osteolysismentioning
confidence: 99%
“…Alveolar bone loss elicited by Porphyromonas gingivalis shares many features of lysis attending OM. Cytokine release (166) as well as induction of RANKL downstream of TLR2 and NOD2 are the prominent pathways leading to osteoclast activation in periodontitis (167,168). IL-17 is also markedly increased in periodontitis and appears to be an important factor in both inflammation and osteolysis of the periodontal tissue (169).…”
Section: Infection-associated Osteolysismentioning
confidence: 99%
“…The major (41-kDa) and minor (67-kDa) fimbriae are distinct types of fimbriae expressed simultaneously by this organism (14,15). The minor fimbriae of P. gingivalis has been reported to induce TNF (TNF-␣), IL-1␤, and IL-6 production in human monocytic cell lines and murine peritoneal macrophages (16,17), although the receptors required for this response have not been defined. The major fimbriae of P. gingivalis are composed of a single subunit protein (fimbrillin), which shares no amino acid sequence homology with any other type of fimbriae (18), and has been shown to be required for adhesion and invasion of fibroblasts and endothelial cells (19 -21).…”
mentioning
confidence: 99%
“…Furthermore, major fimbriae interrupt the host immune system by inducing human peripheral macrophages and neutrophils to overproduce several proinflammatory cytokines such as interleukin-1 (IL-l), IL-6, and tumor necrosis factor alpha (12,13). Although the role of minor fimbriae in P. gingivalis virulence is less well understood, Hiramine et al (6) have shown that the 67-kDa fimbrial protein induces IL-1␣, IL-1␤, and tumor necrosis factor alpha expression in mouse peritoneal macrophages, suggesting their possible involvement in the inflammatory response during the development of periodontal disease. Recent research has shown that minor fimbriae are necessary for the development of P. gingivalis biofilms on streptococcal substrates (7).…”
mentioning
confidence: 99%